2017
DOI: 10.1002/suco.201700009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies and analysis on compressive strength of normal‐weight concrete at low temperatures

Abstract: The construction of liquid nitrogen gas storages and engineering structures in cold regions exposed reinforced concrete structures to low temperatures. This paper investigates the compressive strength of normal‐weight concrete under low temperatures to −165°C through a 174‐specimen test program. The key parameters studied in this test program included low temperature T ranging from −165 to +20°C, water/cement ratio ranging from 0.33 to 0.57, and water content Wc ranging from 0 to 6%. Their influences on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Simple increase in secondary liner thickness cannot completely control the creep deformation in rock mass. FC-based members embedded between primary support and secondary liner can notably bear deformation pressure, thereby the high compressibility and [36,107,131,167,[194][195][196][197][198][199][200][201][202][203][204][205]. [232] was adopted in liner system of Tiefengshan No.…”
Section: Structure Membermentioning
confidence: 99%
“…Simple increase in secondary liner thickness cannot completely control the creep deformation in rock mass. FC-based members embedded between primary support and secondary liner can notably bear deformation pressure, thereby the high compressibility and [36,107,131,167,[194][195][196][197][198][199][200][201][202][203][204][205]. [232] was adopted in liner system of Tiefengshan No.…”
Section: Structure Membermentioning
confidence: 99%
“…Drawing an analogy with plain or traditionally reinforced concrete under these conditions, an increase in compressive and tensile strength can be expected [ 53 , 54 ] along with the embrittlement of a concrete matrix [ 55 ]. Taking into account the increased tensile strength of the material, sufficient ductility to the structural element must be provided by the reinforcement once cracking occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Repetition of this process leads to formation of microcracks, breakdown of wall structure, and damage to concrete or mortar . Damage to concrete due to freezing and thawing also deteriorates its mechanical properties and fracture behavior . The results of previous researches indicate that concrete elasticity modulus decreases when the number of cycles increases .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Damage to concrete due to freezing and thawing also deteriorates its mechanical properties and fracture behavior. [18][19][20][21] The results of previous researches indicate that concrete elasticity modulus decreases when the number of cycles increases. 22 It is also indicated that the fracture energy of concrete after number of cycles is lower than original value before cycling.…”
Section: Introductionmentioning
confidence: 99%